Thermal Performance Augmentation of Double-Pipe Heat Exchanger-A Critical Review - Md Atiqur Rahman (Journal of Heat and Mass Transfer Research)
The increasing demand to enhance the efficiency of heat exchangers has sparked numerous investigations aimed at increasing heat transfer rates while simultaneously reducing the size and cost of industrial equipment. Among the various apparatus utilized in different industries, the double-pipe heat exchanger has garnered significant attention due to its simplicity and versatile applications. Over recent years, numerous meticulous and invaluable studies have delved into double-pipe heat exchangers. This review meticulously analyzes the developmental trajectory of this heat exchanger type while extensively discussing methods for enhancing heat transfer within these systems. In striving to present a comprehensive overview, the authors have meticulously gathered information on various enhancement methods, including active and passive. Recent studies exploring passive heat transfer augmentation methods in double-pipe heat exchangers have been summarized. These methods are summarized under surface modification (like dimples, vortex generators, and protrusion), inserts (like twisted tapes and helical coil), and extended surfaces (like fins and baffles). The prime objective of the current study is to organize the literature related to combining different heat transfer augmentation methods. An additional section on alternating cross-sectional tubes used in double-pipe heat exchangers has been summarized, exhibiting increased vorticity without vortex generator devices. Longitudinal vortices are created throughout the tube's length, leading to a notable improvement in its thermal efficiency. Furthermore, detailed discussions on using Nanofluids in these heat exchangers are provided. Additionally, correlations, primarily focusing on the Nusselt number and pressure drop coefficient, are presented within this review. This comprehensive review is anticipated to offer valuable insights for future investigations in this field.